2023
DOI: 10.1097/meg.0000000000002607
|View full text |Cite
|
Sign up to set email alerts
|

The impact of nonalcoholic fatty liver disease on inflammatory bowel disease-related hospitalization outcomes: a systematic review

Abstract: Evidence suggests that patients with inflammatory bowel disease are at higher risk of developing nonalcoholic fatty liver disease (NAFLD). However, there is limited information currently available on how NAFLD may affect the clinical course of IBD. Thus, we conducted a systematic review to evaluate the impact of NAFLD on IBD-related hospitalization outcomes. All observational studies assessing IBD-related hospitalization outcomes in patients with NAFLD were included. Exclusion criteria were studies published i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The clinical course of gut inflammation itself seems to be negatively influenced by NAFLD occurrence. In a recent systematic review analyzing the impact of NAFLD on IBD-related hospitalization outcomes, Boustany et al highlighted how NAFLD may be related to worse outcomes in individuals with IBD, despite the low quality of available data [ 8 ]. In addition, in a recently published study, Hyun et al estimated the presence of liver steatosis by calculating the Hepatic Steatosis Index (HSI) and Fibrosis-4 (FIB-4) in a cohort of 3356 IBD patients and found that steatosis was associated with increased risk of clinical relapse both in UC and CD patients [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical course of gut inflammation itself seems to be negatively influenced by NAFLD occurrence. In a recent systematic review analyzing the impact of NAFLD on IBD-related hospitalization outcomes, Boustany et al highlighted how NAFLD may be related to worse outcomes in individuals with IBD, despite the low quality of available data [ 8 ]. In addition, in a recently published study, Hyun et al estimated the presence of liver steatosis by calculating the Hepatic Steatosis Index (HSI) and Fibrosis-4 (FIB-4) in a cohort of 3356 IBD patients and found that steatosis was associated with increased risk of clinical relapse both in UC and CD patients [ 9 ].…”
Section: Introductionmentioning
confidence: 99%